Genetic bases and clinical manifestations of coenzyme Q10 (CoQ10) deficiency. Issue 1 (5th August 2014) - Desbats, Maria Andrea; Lunardi, Giada; Doimo, Mara; Trevisson, Eva; Salviati, Leonardo
Abstract: Coenzyme Q10 is a remarkable lipid involved in many cellular processes such as energy production through the mitochondrial respiratory chain (RC), beta‐oxidation of fatty acids, and pyrimidine biosynthesis, but it is also one of the main cellular antioxidants. Its biosynthesis is still incompletely characterized and requires at least 15 genes. Mutations in eight of them ( PDSS1, PDSS2, COQ2, COQ4, COQ6, ADCK3, ADCK4, and COQ9 ) cause primary CoQ10 deficiency, a heterogeneous group of disorders with variable age of onset (from birth to the seventh decade) and associated clinical phenotypes, ranging from a fatal multisystem disease to isolated steroid resistant nephrotic syndrome (SRNS) or isolated central nervous system disease. The pathogenesis is complex and related to the different functions of CoQ10 . It involves defective ATP production and oxidative stress, but also an impairment of pyrimidine biosynthesis and increased apoptosis. CoQ10 deficiency can also be observed in patients with defects unrelated to CoQ10 biosynthesis, such as RC defects, multiple acyl‐CoA dehydrogenase deficiency, and ataxia and oculomotor apraxia. Patients with both primary and secondary deficiencies benefit from high‐dose oral supplementation with CoQ10 . In primary forms treatment can stop the progression of both SRNS and encephalopathy, hence the critical importance of a prompt diagnosis. Treatment may be beneficial also for secondary forms, although with less striking results. In this review we will focus on CoQ10 biosynthesis in humans, on the genetic defects and the specific clinical phenotypes associated with CoQ10 deficiency, and on the diagnostic strategies for these conditions.